Lingual Thyroid: A rare case report - Bhadoria, S; Lavania, A; Saxena, R (Journal of College of Medical Sciences-Nepal, 2012)
Lingual Thyroid is rare developmental anomaly usually affecting females it is usually located in midline, in base of the tongue and represent the faulty migration of thyroid gland although the exact pathogenesis of this ectopic accessory thyroid tissue is not known it generally originates from the epithelial tissue of non obliterated thyroglossal ductus in this report a case of lingual thyroid in a 28 year old patient with difficulty in swallowing and foreign body sensation complaints for 3 years is presented ultrasound showed absent Thyroid in Neck. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6708 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 39-42